Ag/Br dual-doped Li6PS5Br electrolyte with superior conductivity for all-solid-state batteries. (1st April 2023) - Jiang, Ziling; Yu, Chuang; Chen, Shaoqing; Wei, Chaochao; Liao, Cong; Wu, Zhongkai; Chen, Shuai; Cheng, Shijie; Xie, Jia
Abstract: Lithium argyrodites electrolyte with high ionic conductivity and relatively lower cost show great potential as candidates for solid-state batteries. Further improvement of their conductivities can accelerate their applications. One of the means to significantly promote the conductivity of Li-ion is dual doping. Herein, Ag/Br dual-doping strategy is applied on Li6 PS5 Br (2.76 mS cm −1 ) to boast its conductivity to 6.15 mS cm −1 for Li5.55 Ag0.05 PS4.6 Br1.4 . The structural variations and chemical/electrochemical stability of the obtained electrolyte are carefully investigated. Li3 InCl6 electrolyte is introduced in the new battery configuration to mitigate the interfacial instability with LiNi0.6 Mn0.2 Co0.2 O2 active material enabling good electrochemical performances. The assembled battery delivers a discharge capacity of 160.8 mAh g −1 for the 1st cycle and maintains 85.9% of the initial value after 50 cycles at 0.5C. This modification strategy was proved effective for increasing the conductivity of sulfide electrolytes in this work. Graphical abstract: AgBr dual-doping on Li6PS5Br (2.76 mS cm−1) yields boasting Li-ion conductivity of up to 6.15 mS cm−1 for Li5.55Ag0.05PS4.6Br1.4 due to the enlargement of diffusion channels for ions and the increase of anion disorders, resulting in excellent electrochemical performances for the corresponding solid-state batteries. Image, graphical abstract